Game-based student response system: Revisiting its potentials and criticalities in large-size classes. (July 2021) - Ranieri, Maria; Raffaghelli, Juliana E; Bruni, Isabella
Instructor–student interaction and regular feedback are seen as teaching strategies designed to support effective learning. These days, there is increasing reliance on technology to support this in the classroom; one such technology is a student response system or its more recent development of this, that is, a game-based one. This study investigates the potential of using game-based student response systems for formative assessment through the analysis of learning outcomes and students' perceptions of the gamified experience in terms of engagement and pleasantness. A quasi-experiment was conducted within an undergraduate course on educational technologies, involving about 400 students. Learning improvements were measured through a pre- and posttest, and students' perceptions were elicited through a questionnaire. Data analysis showed a high level of student satisfaction and an overall improvement of learning outcomes due to the use of game-based student response systems. However, differences in terms of effectiveness were found according to the nature of the topics dealt with in the course, that is, whether or not they were used in the development of theoretical knowledge rather than the use of that knowledge in a more practical context.